On Ad-Nonprojection Method for Stable Approximation to Infinite-Dimensional Moore–Penrose Inverse. (25th October 2020) - Du, Nailin; Gan, Shanlin
Abstract: This note presents ad-nonprojection method for approximation to infinite-dimensional Moore-Penrose inverse, which includes generalized projection method as a special case. The main result (Theorem 4) gives characteristics of perfect convergence, weak perfect convergence, and uniform perfect convergence of ad-nonprojection method. This result is a generalization of several fundamental theorems known.